Physicochemical degradation of Avicennia marina mangrove soils in the Red Sea: implications for coastal ecosystem services - Bajahmoum, Emtnan Ahmad; Almaghamsi, Afaf (Frontiers in Soil Science, 2025)
Mangrove ecosystems are remarkable coastal environments that thrive at the interface between land and sea, playing a crucial role in maintaining ecological balance and safeguarding coastal agricultural and fisheries productivity through erosion control, nutrient cycling, and salinity buffering. The physicochemical properties of mangrove soils underpin the health of these ecosystems, particularly for Avicennia marina, a keystone species critical to coastal resilience and habitat provisioning. However, anthropogenic disturbances threaten their sustainability and compromise their ability to deliver vital ecosystem services. Soil samples from undisturbed (Southern Corniche, Jeddah) and disturbed (Masturah) mangrove sites were analyzed for physicochemical characteristics to assess potential anthropogenic impacts along Saudi Arabia’s Red Sea coast. From six locations (undisturbed: Jeddah, n=3; disturbed: Masturah, n=3) soil samples were analyzed for texture, pH, electrical conductivity (EC), total dissolved solids (TDS), water content (%WC), total nitrogen (TN), phosphorus (TP), organic carbon (TOC), macronutrients (Na+, Ca²+, Mg²+, K+), and cation exchange capacity (CEC). Undisturbed soils exhibited significantly higher moisture, TN, TP, and TOC—key indicators of nutrient retention and carbon sequestration capacity—while disturbed soils were more alkaline, a condition linked to diminished nutrient cycling and plant stress. Macronutrient distribution (Na+ > Mg²+ > Ca²+ > K+) remained consistent across sites, suggesting salinity-driven nutrient imbalances may limit mangrove recovery. These findings highlight how soil degradation in disturbed mangroves reduces their ability to stabilize sediments, mitigate saltwater intrusion, and sustain fisheries nurseries, directly impacting coastal communities. Moreover, these soil changes reduce mangrove capacity to buffer adjacent farmland from salinization and erosion, threatening agricultural productivity and undermining carbon sequestration goals central to climate mitigation. To enhance ecosystem resilience, we recommend the application of soil organic amendments and the strategic conservation of high-carbon mangrove zones, in alignment with Saudi Arabia’s Vision 2030 sustainability framework. This study highlights the critical importance of safeguarding mangrove soils as foundational natural infrastructure for climate adaptation and food security in arid coastal environments.